Integrating Human Safety and Environmental Protection into Supply Chain Operations for a Sustainable Future - Saxena, Richa; Sharma, Kajal (Journal of Economics and Management, 2026)
The paper examines the critical success factors for integrating environmental protection and human safety into supply chain operations for a sustainable future. Ninety-one supply chain managers and sustainability officers from the retail, logistics, and industrial sectors completed a questionnaire-based data collection process. The survey examined organizational procedures, perceived obstacles, and facilitators for the integration of environmental and human safety. A thematic analysis of the responses revealed that successful integration requires strong leadership commitment, comprehensive safety management systems, supplier cooperation, and continuous training. Lack of resources and inconsistent standards appeared as major obstacles, although regulatory compliance and stakeholder pressure were also noted as important drives. The results highlight the significance of proactive supplier engagement, integrating environmental and safety objectives into procurement procedures, and cultivating a shared responsibility culture across the supply chain. By highlighting practical elements that businesses can use to improve both environmental protection and human safety in their operations, for a sustainable future, this study contributes to the growing body of knowledge on sustainable supply chain management.